Fractional‐Order Localized Spoof Surface Plasmons for In‐Phase or Out‐of‐Phase Power Division. Issue 1 (18th November 2022) - Li, Si‐Qi; Li, Fan‐Hong; Zhu, Yu; Du, Chao‐Hai
Abstract: Localized spoof surface plasmons (LSSPs) are extensively used to develop various functional components due to their excellent characteristics of subwavelength confinement and concomitant near‐field enhancement. In this paper, a rat‐race coupler based on fractional‐order LSSPs is proposed to achieve in‐phase or out‐of‐phase power division. It is a four‐port passive component with the advantage of miniaturization. In simulation and experiment, the feasibility of the rat‐race coupler is demonstrated and the existence of the rare fractional‐order LSSPs modes is conformed. More interestingly, a general design method is suggested, based on which arbitrary fractional‐order LSSPs modes can be constructed by skillfully tailoring the electrical lengths between ports. This paper expands the applications of the LSSPs and enriches the topological properties of the LSSPs. Abstract : In this paper, a rat‐race coupler based on fractional‐order localized spoof surface plasmons (LSSPs) is proposed to achieve in‐phase or out‐of‐phase power division. Arbitrary fractional‐order LSSPs modes are constructed by masterfully tailoring the electrical lengths between ports.